Trabalho, ética e saúde mental: uma análise a partir das representações sociais de servidores públicos de uma universidade - Maffioletti, Gabriella Suzana Lorenzzon (2023)
This study is inserted in the mental health and work interface at the university. We found that mental illnesses in university public servants are one of the main reasons for absence from work and this motivated us to seek to understand this reality. As a thesis, we consider that there is an ethical dimension involved in work. At the university, this dimension would be linked to the recognition of the role of education and science as a way to change a society. Considering that work at universities is important and has a positive function both for those who exercise it and for society in general, we seek to understand whether there is a relationship between ethics and the worker's mental health. Our problem lies in the idea that the ethical dimension of work represents the worker's recognition that his work and the result he obtains from it had a social significance. We seek to know if this ethical dimension of work is verified in the context of the public university and if there is a relationship between it and the maintenance or improvement of the mental health of the servers. For this, we base the research proposal on the psychodynamics of work, in addition to placing ethics within the reality of practical life, that is, as well-doing within a contingency context, which is life itself. We used the theory of social representations as a research, capture and data analysis technique. We conducted interviews with 32 employees of a federal and public university in Francisco Beltrão/PR, extracting the social representations about work. We analyze it in relation to the concepts of health and ethics involved in this theme. In addition, we researched institutional projects and programs related to mental health and work at the same university. We also sought and analyzed legislative acts related to mental health and the work of public servants in universities. We conclude that there is an ethical dimension in social representations about work. It is involved in the cognitive project that precedes the work itself, where there is not only the technical intention of accomplishing something, but rather the need to put into effect, through the work itself, a series of important values for the worker, values that are tributaries of a social and personal context. In the cognitive sphere of work, there are the values that, even derived from culture, are individually modulated and hierarchized. Ethics is constituted, for the research group, in the correlation between the values of being useful and generating a positive impact through one's own work (doing good for oneself and for the world); quest for justice; need for cooperation and personal identification/enjoyment for the activity. This panorama of values may or may not be put into practice in the work environment. The more this environment, work circumstances and the ability to exercise prudence allow living according to the scenario, the happier the worker will be and the potential for promoting mental health will be increase.